Workflow in collaborative learning - Abdullah, Rusli (2000)
The usage of network computer technology in term of workflow computing or called supporting collaborative of work (CSCW) nowadays is very importance. There are a lot of applications that can be develop by using the prototyping approach for supported collaborative of work that are based on usage and requirement. This paper will covers on the concept and architecture of workflow in the implementing collaborative of learning, it’s beneficial and impacts of the implementation of those applications in an organization. The applications are also being developed by using a selected tool that’s available in the market which is supported the collaborative of learning environment.